Building unconventional RC vehicle - Ang, Choong Hwee (2016)
The main purpose for this project would be to explore more of unconventional vehicles which are designed in a manner that goes beyond what is deemed normal. The reasons for building these designs are to aid people to solve problems that they face in a way that conventional vehicles are unable to perform. There are three main sectors a vehicle is typically classified under. They are aerial, land, and sea vehicles, while some are classified in between two sectors, for example, amphibious vehicles. This report aims to focus on the area around constructing of aerial and land unconventional vehicles each which will help in engaging students and youngsters to be more exposed to DIY implementations of unmanned systems. This report will include findings for the base idea, design, print and explanation of method and the assembly for the project in detail.